Steroid utility, immunotherapy, and brain tumor management: an update on conflicting therapies - Matthew Goldman; Brandon Lucke-Wold; Meleine Martinez-Sosa; Jason Katz; Yusuf Mehkri; Jeff Valisno; Stephan Quintin (Open Exploration Publishing Inc., 2022)
Steroid use is a widely accepted practice for both the treatment and prevention of tumor-induced edema, but there are many unknowns regarding their current clinical utility with modern anti-tumor therapies. This decreases edema and relieves the symptomatic mass effect. There are clearly understood benefits and commonly accepted complications of methylprednisolone (MP) use, but the topic is recently controversial. With immunotherapy advancing, a robust immune response is crucial for full therapeutic efficacy. The immunosuppression of MP may interfere with future and current therapeutics relying on the integrity of the patient's immune system. This further emphasizes the need for alternative agents to effectively treat tumor-induced cerebral edema. This review highlights the current clinical utility of steroids to treat brain tumor-related edema and the underlying pathophysiology. It also reviews details regarding different steroid formulations and dosing. Research available regarding concurrent steroid use with immunotherapy is detailed next, followed by alternatives to steroids and barriers to their adoption. Finally, this paper discusses pre-clinical findings and emerging treatments aimed to augment or replace steroid use.